Psalm 51 and the criticism of the cult : does this reflect a divided religious leadership? - Groenewald, Alphonso (Old Testament Essays, 2009)
The aim of this publication will be twofold : Firstly, to view Psalm 51, especially those verses which can be designated as cult-critical. Secondly, to indicate that the prophetic critique is part of a larger prophetic rhetoric to convict of sin, to explain God's plan, and to indicate the hope of salvation. The cult criticism of Psalm 51:18-19, however, is not a repudiation of the cult and cultic practices : the fact that a later redactor added the last two verses (Ps 51 : 20-21) after verses 18-19, proves this point. Therefore, it would be incorrect to see the prophetic critique of the priesthood as a sign that the priests and the prophets were incompatible, or that the prophets wanted to discredit and discard the temple cult.
free